Development of an operational productivity tool within a cancer treatment center pharmacy. - Achey, Thomas S.; Riffle, Allison R.; Rose, Robert M.; Earl, Marc (American Journal of Health-System Pharmacy, 2018)
Purpose. The development and implementation of an operational productivity tool in an academic cancer treatment center are described. Summary. Based on the increasing complexity of care delivery within the oncology setting, solutions were explored within Cleveland Clinic pharmacy's productivity model. Data were electronically captured based on orders processed through the outpatient oncology setting, including hazardous and nonhazardous medications. Based on current workflow, inpatient and outpatient orders were reviewed in productivity metrics. The metric defining the variability of the workload itself was weighted dispense type as it was the best representation of a mixed-skill workflow. After conducting workflow process mapping, discrete measurable steps were assessed and evaluated daily. Operational components of interest included pharmacist verification activities and technician compounding activities. Historical production data were sampled for assigning relative value units (RVUs) respective to time to normalize workload into a common unit (i.e., 1 hour) and to relate work demand in a highly variable setting. RVUs were assigned and delineated by cognitive and distributive activities for pharmacists and technicians, respectively. The Cleveland Clinic department of pharmacy developed a productivity tool to retrospectively measure workload involving time to review, verify, reconstitute, admix, and deliver chemotherapeutic agents. The weighting of each medication allowed for precise and meaningful evaluation of productivity. With RVUs assigned to 2 years of operational metrics, there now exists an opportunity to monitor performance trends within the cancer treatment center pharmacy. The data are readily retrievable within the electronic health record. Conclusion. The productivity data provided precise information to assess trends in operations within the pharmacy of an outpatient cancer treatment center.